Kondisi Sosial Ekonomi Pekerja pada Objek Wisata One Moba’a - Hasrawati Hasrawati; La Harudu; Surdin Surdin; Andrias Andrias (Jurnal Penelitian Pendidikan Geografi, 2025)
Tomia District is one of the two districts located on Tomia Island, Wakatobi Regency. The district offers various marine tourism destinations that captivate visitors, one of which is the One Moba’a tourist attraction. This study aims to: 1) examine the social conditions of workers at the One Moba’a tourist attraction in Tomia District, Wakatobi Regency, and 2) analyze their economic conditions. This research employed a descriptive quantitative method with percentage analysis as the data analysis technique. The findings reveal that the income level of workers at the One Moba’a tourist attraction generally falls into the medium category. Furthermore, most workers already have decent housing that meets several livability criteria, with the majority owning their homes. In terms of educational background, most workers have relatively high education levels, with the highest completed level being senior high school. The implication of this study is that the improvement of workers’ welfare in the marine tourism sector is not solely determined by income levels, but also by educational support, asset ownership, and stable social conditions. Therefore, the results of this research can serve as a reference for local governments and tourism managers in formulating sustainable tourism development strategies that not only focus on increasing tourist visits but also on enhancing the quality of life of the workers involved.